Implementation of the projek penguatan profil pelajar pancasila (p5) integrated into fourth-grade natural and social sciences (ipas) learning in elementary schools within the raflesia school cluster - Siwi Utaminingtyas; Windarni Lestari; Atika Dwi Evitasari (Jurnal Ilmiah Pendidikan Dasar, 2026)
Through the Merdeka Curriculum, the Projek Penguatan Profil Pelajar Pancasila (P5) is integrated into Natural and Social Sciences (IPAS) learning to support the development of students’ character and competencies. However, its implementation in elementary schools continues to face various challenges. This study aimed to analyse the implementation of P5 in IPAS learning, identify the challenges encountered, and describe the efforts made to overcome these challenges in public elementary schools within the Raflesia Cluster, Borobudur District. This study employed a descriptive qualitative approach involving principals and fourth-grade teachers from SD Negeri Tuksongo 1 and SD Negeri Tanjungsari as the research participants. The research utilised semi-structured interviews, non-participant observations, and document reviews as sources of data. Analysis was conducted systematically through the stages of qualitative data processing, including data reduction, presentation of findings, and verification of conclusions. The study findings indicated that the implementation of P5 within IPAS learning was conducted through six sequential phases, including understanding P5, preparing the school ecosystem, planning and implementing projects, documenting and reporting outcomes, and conducting evaluation processes and planning subsequent follow-up actions. The main challenges included limited learning facilities and infrastructure, insufficient instructional time, teachers' limited ability to integrate Pancasila Student Profile elements embedded in IPAS learning activities, difficulties in developing project modules and assessments, and differences in students' characteristics. To address these challenges, schools enhanced teachers' competencies through professional training, utilised the surrounding environment as a learning resource, improved learning facilities, strengthened coordination among school stakeholders, and provided continuous guidance to students during project implementation. These findings indicate that integrating P5 into IPAS learning has the potential to strengthen students' character while enhancing their competencies, provided that it is supported by competent teachers, adequate school readiness, and effective project-based learning management.